Vivências de mães com filhos portadores de fibrose cística - Cordeiro, Samara Macedo (2013)
The Cystic Fibrosis or mucovicidose is a chronic disease, autosomal recessive, hereditary. Living with a child with Cystic Fibrosis can change the whole dynamic of life of a mother. This study aimed to understand the experience of mothers who have children with cystic fibrosis, and thus reveal the phenomenon of being a mother of Cystic Fibrosis. We adopted a qualitative methodology with a phenomenological approach. The subjects were eight mothers of children with Cystic Fibrosis in southern Minas Gerais. Data collection was conducted through audio recorded interview from June to October 2012. Approved by the Research Ethics Committe of UNIFAL-MG under the protocol number 017/2012. A questionnaire was used to characterize the subjects in order to prepare a biography of each mother and thus provide the reader closer to the phenomenon. We used the following guiding question: Would you told me her experience as a mother of a child with cystic fibrosis. How is living day to day this experience? The data were discussed based on some of the theoretical assumptions of Martin Heidegger and authors who worked the theme. After analysis of the interviews revealed three categories and two subcategories which represent the essence of the experiences of mothers of children with cystic fibrosis in their day-to-day: The Being-there experiencing the diagnosis of cystic fibrosis in his son; Experiencing caution when child with cystic fibrosis which is divided into: Being-mother experiencing treatment, Changing your life-world and family dynamics; Before the child’s future: between anguish and hope. The results showed that live the experience of being a mother of a child with cystic fibrosis goes through moments of fear, doubt and uncertainty. The stage of diagnosis had a major impact both in being the mother in the family as a whole. The daily life of the family have changed and been adapted prioritizing the care of the sick child and the future looks very uncertain in the life of this mother. The knowledge unveiled here brings forward a new vision to the real needs of these mothers, makes us realize that each person is unique and must be attended at all its peculiarities. In this sense, the experience of mothers with children with Cystic Fibrosis described in this study may provide a basis for reflections practices of between nurses and other health professionals serving these clients, making them reflect on how to care provided to them, so that they can bring about changes of care to these mothers, making it more human and welcoming.